Evaluation of Association between Vaginal Infections and High-Risk Human Papillomavirus Types in Female Sex Workers in Spain. (31st July 2012) - Rodriguez-Cerdeira, C.; Sanchez-Blanco, E.; Alba, A.
Abstract : Background . Infection with and persistence of high-risk human papillomavirus (HR-HPV) are the strongest risk factors for cervical cancer. In addition, other genital microorganisms may also be involved in the progression of HPV-associated lesions. Objetive . To evaluate the association of the vaginal microbiota ( Candida spp., Trichomonas vaginalis, and bacterial vaginosis) with HR-HPV infection in Spanish female sex workers (FSWs). Methods . This cross-sectional study involved 208 (FSWs; age, 18–49 years) who visited a sexually transmitted infection (STI) information and prevention center (SERGAS) between January 2010 and December 2011. Face-to-face interviews were carried out. Cervical and vaginal samples were examined for human papillomavirus (HPV), Trichomonas vaginalis, Candida spp., and microorganisms related to bacterial vaginosis (BV). Results . HR-HPV was found to be significantly associated with BV in FSWs with positive results for HPV16-related types (31, 33, 35, and 52). T. vaginalis was isolated in FSWs with the following HR-HPVs: 18, 45, 66, and 68. Candida spp. were isolated only in FSWs with HPV 18-positive infection. Conclusion . We demonstrate a significant prevalence of HR-HPVs in FSWs with disturbances in the vaginal microbiota.